Evaluación Del Efecto Del Agua Magnetizada En La Segunda Fase Floración - Cosecha Del Amaranto (Amaranthus Caudatus L) Variedad Selenaya Sosulka, CEASA - Latacunga - Cotopaxi, 2021- 2022. - Arias Mullo, Danilo Salomón (2022)
This research study was conducted with the purpose of evaluating the effect that the magnetized water had when applied to the Amaranth crop. The general objective was to analyze the effect of the magnetized water in the second phase of flowering until the harvest of amaranth (Amaranthus Caudatus L.) of the Selenaya Sosulka variety. The experimental design was a completely randomized block design with four treatments and four repetitions, obtaining 16 experimental units, and the results presented were as follows: the water analyzed after being exposed to magnetization shows that there is variation showing changes in chemical properties compared to untreated water. The water parameters change when subjected to magnetic fields, as a result the pH decreases as the intensity of the magnets increases with a pH of 7.57 and a hardness of 147 in Treatment T4. On the other hand, the treatment with the highest efficiency is T3, the PH level drops notoriously to 7.23 and with a hardness level of 160, which is moderately hard. In the degree of restriction in relation to electrical conductivity from 656 to 670. The soil parameters do change when water is supplied to the soil subjected to magnetic fields, in the PH and electrical conductivity results, the PH is 8.16 and an EC of 0.39 for the T3 treatment. Treatment T1 increased the PH to 8.32 and increased its level to 0.41 in electrical conductivity. Regarding agronomic variables, the following results were obtained. Treatment T3, which corresponded to water subjected to magnetic fields with an intensity of 5000 gauss, gave better results in terms of variables such as panicle diameter, root volume, and harvest data such as panicle weight. On the other hand, treatment T1, which corresponded to water subjected to a magnetic intensity of 1000 gauss presented good variants results such as plant height, panicle diameter, chlorophyll content, and seed weight. Therefore, it was possible to conclude that water, when subjected to a magnetic field of 1000 gauss, which was low intensity, presented better results in most of the variants, while the T3 treatment, which is water subjected to magnetic fields of 5000 gauss, presented favorable results in the important variants described above. The impact of the magnetic field on Amaranth plants was researched by means of drip irrigation, the results revealed useful effects on agronomic variants.